Finite Element Analysis for Large Deformation Frictional Contact Problems with Finite Sliding - HISADA, Toshiaki; NAKAMURA, Kazuhiro; CHEN, Xian; MORI, Masahiko (Transactions of the Japan Society of Mechanical Engineers Series A, 1998)
In the analysis of frictional contact problems with large deformation, use of convected coordinate system is a natural approach, by which the frame indifference of friction law can be maintained. However, in the case of finite element method, a problem arises due to the discontinuity of the local coordinates between elements when the sliding extends over the element boundary. In this work a method is proposed to solve this problem, i.e., although the formulation is essentially based on a convected coordinate system. the sliding term is re-defined as a spatial vector and is calculated using the reference configuration. Thus, the finite sliding due to large deformation can be treated regardless of the limitation of element coordinate systems. Also, the corresponding consistent tangent stiffness is derived to obtain quadratic convergence. The effectiveness of the proposed method is verified by a couple of numerical examples including an elasto-plastic frictional contact problem with large deformation.